Impact of environmental friendly perception of tourists on their visit intention: a study on surf hotel bentota, sri lanka - Nissanka, E.G.R.W. (University of Jaffna, 2016)
This study, which is centered on a widespread review of literature, aims to probe how does the environmental friendly perceptions of tourists, impact on tourists' their visit intention for tourists hotels. The fundamental reason for conducting the research was to investigate the cause for receiving much importance as a green destination among the other hotels in the area and to examine whether tourists' environmental friendly perceptions have an influence on it. Attitudes, subjective norms, perceived behavioral control and environmental concern are identified as the underpinning dimensions for the environmentally friendly perception. Stratified random sampling method was used to distribute the questionnaire among the sample which has been used 221 respondents within the visitors of the hotel. This study used the multiple regression analysis to show the impact of environmental friendly perceptions towards tourists' visit intention. The discussion reveals that tourists' environmental concern does not have a significant impact on visit intention while the other three dimensions namely attitudes, subjective norms and perceived behavioral control have a significant impact on visit intention by analyzing the results. Moreover, attitude dimension seems to have the highest impact on visit intention. This research will make a positive contribution on understanding how the direction of environmental friendly practices influences on tourists' visit intention.
Keywords: Environmental friendly perceptions; Visit intention; Tourism industry